RirA of Dinoroseobacter shibae senses iron via a [3Fe–4S]1+ cluster co-ordinated by three cysteine residues. Issue 1 (10th January 2020) - Behringer, Maren; Plötzky, Lisa; Baabe, Dirk; Zaretzke, Marc-Kevin; Schweyen, Peter; Bröring, Martin; Jahn, Dieter; Härtig, Elisabeth
Abstract : In the marine bacterium, Dinoroseobacter shibae the transcription factor rhizobial iron regulator A (RirA) is involved in the adaptation to iron-limited growth conditions. In vitro iron and sulfide content determinations in combination with UV/Vis and electron paramagnetic resonance (EPR) spectroscopic analyses using anaerobically purified, recombinant RirA protein suggested a [3Fe–4S] 1+ cluster as a cofactor. In vivo Mössbauer spectroscopy also corroborated the presence of a [3Fe–4S] 1+ cluster in RirA. Moreover, the cluster was found to be redox stable. Three out of four highly conserved cysteine residues of RirA (Cys 91, Cys 99, Cys 105) were found essential for the [3Fe–4S] 1+ cluster coordination. The dimeric structure of the RirA protein was independent of the presence of the [3Fe–4S] 1+ cluster. Electro mobility shift assays demonstrated the essential role of an intact [3Fe–4S] 1+ cluster for promoter binding by RirA. The DNA binding site was identified by DNase I footprinting. Mutagenesis studies in combination with DNA binding assays confirmed the promoter binding site as 3′-TTAAN10AATT-5′. This work describes a novel mechanism for the direct sensing of cellular iron levels in bacteria by an iron-responsive transcriptional regulator using the integrity of a redox-inactive [3Fe–4S] 1+ cluster, and further contributes to the general understanding of iron regulation in marine bacteria.